Gadamers Hermeneutische Kunstauffassung - Csaba Olay (Estetika, 2008)
Art is no arbitrary topic in Hans-Georg Gadamer’s philosophical hermeneutics. Rather, it is a fundamental phenomenon, the description of which constitutes an unavoidable task of philosophy. In this article the author seeks to demonstrate the importance of art in philosophical hermeneutics, and in two major steps develops a hermeneutical conception of art. First, the author discusses the concept of the truth of art with special attention to the view that art can be described as the cognition of essence. Second, the ontology of the work of art is analyzed in detail, focusing on Gadamer’s basic idea that the work of art becomes accessible, strictly speaking, only in its presentation. Abstrakt Kunst ist kein beliebiges Thema neben anderen in Hans-Georg Gadamers philosophischer Hermeneutik, sondern ein grundsätzliches Phänomen, dessen Beschreibung eine unvermeidliche Aufgabe der Philosophie bildet. Der Aufsatz zeigt die Bedeutung der Kunst für die Hermeneutik und erörtert danach die hermeneutische Kunstauffassung in zwei Schritten. Zuerst wird die Wahrheit der Kunst ausführlich dargestellt, mit besonderer Rücksicht auf die These, der zufolge die Kunst sich als eine Wesenserkenntnis bestimmen lässt. Danach wird die Ontologie des Kunstwerks mit dem zentralen Gedanken, dass ein Kunstwerk eigentlich nur in seiner Darstellung zugänglich ist, detailliert behandelt.